Community empowerment in landslide management in Sonyo hamlet - Iswanto Suwarno; Muhammad Ahmad Baballe; Irfan Ahmad; Erwin L. Rimban; Mohammad Aljanabi; Robbi Rahim; Anggia Arif; Nia Maharani Raharja; Nurhayati Nurhayati (Peneliti Teknologi Teknik Indonesia, 2021)
Soyo Hamlet is led by Mr. Suranto as the head of the hamlet. The hamlet itself consists of eight RTs with 173 family heads. The hamlet is located in a mountainous area in the Kulon Progo district. Soyono Hamlet is bordered by Sidomulyo Hamlet and Mount Kelir Hamlet. Soyo Hamlet, which is located in a mountainous area, has many problems. One of the problems that have come to our attention is the problem of vulnerability to natural disasters. Natural disasters that often occur in the village are landslides. It is feared that in the rainy season like today, heavy rains can cause landslides. Based on the above problems, this community service designs and implements a landslide early warning tool. This tool is made using the main component is a microcontroller which is used as a data processor, a sensor uses a potentiometer to detect ground movement, and a siren. In addition to installing landslide equipment, this community service also provides lessons on landslide recovery